(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
This paper applies a new Breast Coordinate System to measure three-dimensional breast movements, relative to the thorax by eliminating the effects of body rotation, translation, bending and tilting during activities. Two-dimensional and three-dimensional breast movement trajectories of pert breasts and ptotic breasts are presented and compared from four different perspectives in both the global and local coordinate systems. The scatter plot of breast displacements against time in x, y and z coordinates were fitted by polynomial functions. The movement amplitude of the ptotic breast is larger than that of the pert breast in all directions. In a vertical direction, the ptotic breast velocity is greater than that of the pert breast one.